Resilience, Work–Family Conflict, and Marital Satisfaction among Couples in Long-Distance Marriages - Dila Chrisseyaningtyas; Arthur Huwae (Universitas PGRI Yogyakarta, 2026)
This study investigates the influence of resilience and work–family conflict on marital satisfaction among couples in long-distance marriages. A quantitative approach using multiple regression analysis was conducted with 118 participants selected through accidental sampling. Data were collected via the Resilience Quotient Scale, Work–Family Conflict Scale, and ENRICH Marital Satisfaction Scale. Findings show that resilience and work–family conflict significantly predict marital satisfaction (F = 16.9, p < 0.001). Resilience accounted for 32.4% of the variance, while work–family conflict explained 41.1%. Higher resilience was associated with greater marital satisfaction, while greater work–family conflict was associated with lower marital satisfaction. Resilience and balanced work–family roles are vital to sustaining marital satisfaction among long-distance couples. These findings emphasize that couples with higher resilience and balanced work–family roles experience stronger marital satisfaction despite physical distance. This research contributes to family psychology literature by emphasizing resilience and role management as key determinants of marital stability in physically separated relationships. Keywords: resilience, work–family conflict, marital satisfaction, long-distance marriage